2008
DOI: 10.1021/ac702626n
|View full text |Cite
|
Sign up to set email alerts
|

Depth Profiling of Organic Films with X-ray Photoelectron Spectroscopy Using C60+ and Ar+ Co-Sputtering

Abstract: By sputtering organic films with 10 kV, 10 nA C60+ and 0.2 kV, 300 nA Ar+ ion beams concurrently and analyzing the newly exposed surface with X-ray photoelectron spectroscopy, organic thin-film devices including an organic light-emitting diode and a polymer solar cell with an inverted structure are profiled. The chemical composition and the structure of each layer are preserved and clearly observable. Although C60+ sputtering is proven to be useful for analyzing organic thin-films, thick organic-devices cannot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 9 publications
2
50
0
Order By: Relevance
“…Sputter depth profiling with energetic Ar-ions (4 keV) provided some information (Figures S7-S10), but information from the C 1s region is of limited use as the bombardment of carbon films is known to cause some chemical changes to the carbon morphologies. 54,55 Additionally, differential charging observed in the synchrotron-based XPS studies support the electrically resistive nature of the Al oxyfluoride (Al-O-F) formed during cycling in the LiClO 4 electrolyte.…”
Section: Discussionmentioning
confidence: 69%
“…Sputter depth profiling with energetic Ar-ions (4 keV) provided some information (Figures S7-S10), but information from the C 1s region is of limited use as the bombardment of carbon films is known to cause some chemical changes to the carbon morphologies. 54,55 Additionally, differential charging observed in the synchrotron-based XPS studies support the electrically resistive nature of the Al oxyfluoride (Al-O-F) formed during cycling in the LiClO 4 electrolyte.…”
Section: Discussionmentioning
confidence: 69%
“…Recent evidence suggests that co-sputtering with C þ 60 and other ion beams, such as Ar þ can prevent the accumulation of damage associated with carbon deposition in the source (Yu et al, 2008), where it has been shown that C þ 60 =Ar þ co-sputtering can be used to extend the depth profile range and maintain a more constant sputter rate in polymer depth profiles. The theory is that the Ar þ gun prevents the deposition of carbon and therefore can both improve the quality of the depth profile and increase the achievable erosion depth.…”
Section: Co-sputteringmentioning
confidence: 99%
“…This has been performed for instance on OLED systems, in which the metallic cathode is removed mechanically before the organic layers analysis [16]. Another approach consists on switching ion sources while crossing hybrid interfaces (e.g., using a monoatomic Ar source on inorganic layers, then switching to Argon cluster ion beams in the organic layers [17]). Finally, hybrid depth profiling with only one source has been attempted on 1.4 to 3.5 nm gold layer embedded in cholesterol deposits [14], sputtered with C 60 + ion source.…”
Section: Introductionmentioning
confidence: 99%